Term limits and legislative representation - Carey, John M. (Cambridge University Press, 1996)
Virtually all legislative theory is built on the assumption that politicians are first and foremost reelection-seekers, and because so few countries have ever limited legislative reelection, this assumption has rarely been questioned. As a result, political science has been ill-equipped to offer insights on the impact of legislative term limits. Term Limits and Legislative Representation tests the central arguments made by both supporters and opponents of such reform by examining the experience of Costa Rica, the only long-term democracy to impose term limits on legislators, and by providing extensive comparisons with legislatures in Venezuela and the United States. Professor Carey challenges claims made about the effects of term limits on political careers, pork barrel politics, and the effectiveness of political parties in passing their programs